2015
DOI: 10.1021/acs.chemmater.5b03904
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Nanoclusters of MgO Coated with Alkali Metal Nitrates/Nitrites for Rapid, High Capacity CO2 Capture at Moderate Temperature

Abstract: Colloidal nanoclusters of metal oxides constitute a promising new class of building blocks for a range of advanced functional materials. Herein, we report on the development of colloidal nanoclusters of MgO for CO2 capture prepared by a novel nonhydrolytic sol–gel reaction followed by the deposition of alkali metal salts by methanol evaporation-induced surface precipitation. The CO2 uptake exceeded 11.7 mmol g–1 (514.8 mg CO2 per 1 g of adsorbent) in 30 min in the presence of 100% dry CO2 under ambient pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
100
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(113 citation statements)
references
References 42 publications
12
100
1
Order By: Relevance
“…However, after coating with 15 mol% (Li-Na-K)NO 3 , the CO 2 uptake slightly increased when the Mg/Al ratio was 5:1 to 9:1, and significantly increased to 2.03 when the Mg/Al ratio was increased to 20:1. Similar results have also been observed by Harada et al [52,53] and Kim et al [51] .…”
Section: Samplessupporting
confidence: 90%
See 1 more Smart Citation
“…However, after coating with 15 mol% (Li-Na-K)NO 3 , the CO 2 uptake slightly increased when the Mg/Al ratio was 5:1 to 9:1, and significantly increased to 2.03 when the Mg/Al ratio was increased to 20:1. Similar results have also been observed by Harada et al [52,53] and Kim et al [51] .…”
Section: Samplessupporting
confidence: 90%
“…It is well known that doping with alkali metal carbonates can further promote the LDHs derived CO 2 adsorbents [52] . However, recently Harada et al [52,53] developed (Li-Na-K)NO 3 molten salt coated MgO particles with enhanced CO 2 capture capacity. Kim et al [51] also reported an NaNO 3 promoted LDH with a Mg/Al ratio of 20 and achieved a high CO 2 capture capacity.…”
Section: Samplesmentioning
confidence: 99%
“…Commonly used strategies to improve the CO 2 capture capacity of MgO include enlarging the surface area [19][20][21][22], changing operation conditions [19,23,24], and incorporating promoters [25][26][27][28][29]. Among these strategies, the use of appropriate promoters has been proved to be most effective so far.…”
Section: ͳǥmentioning
confidence: 99%
“…The large active cluster surface area has also been exploited in CO 2 -capture experiments, using clusters formed from MgO NPs. [137] The rapid conversion of MgO to MgCO 3 was reversible, and was further enhanced by coating of the clusters with alkalimetal nitrate salts, opening a potential pathway for flexible CO 2 storage.…”
Section: Separation and Enrichment Applications Of Npcsmentioning
confidence: 99%